PENERAPAN PENDEKATAN KONTEKSTUAL UNTUK MENINGKATKAN PENGUASAAN KONSEP PADA MATERI BENTUK ALJABAR - Cindy Noviani; Masta Hutajulu; Gida Kadarisma (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
The ability to master concepts is one of the obstacles experiences by students in studying algebraic form. This is the background of the author to conduct this research with the aim of knowing the increase in students conceptual mastery if a contextual approach is applied to learning algebraic form in class VII Junior High School of Dharma Kartini Cimahi. The type of research used is Classroom Action Research (CAS) with the methods use are survey, test, and observation methods, the analysis used is qualitative. The results of the stude are evidenced by the improvement in student learning outcomes from the condition of learning completeness that no one reaches the KKM value, increasing in the first cycle as many as 8 students (40%) and in the second cycle it has increased to 15 students (75%). It can be concluded that the application of the contectual approach is good enough to improve students mastery of concepts in algebraic form.